Modelling of the Russian– American Relations Is Possible - A. G. Savoysky (Vestnik MGIMO-Universiteta)
This article is devoted to a new scientific theory about the possible modelling of the relations between Russia and the United States. On the basis of the research conducted on two centuries of Russian-American relations, universal political science hypothesis about 14- year cyclicality of the international bilateral relations is also put forward.